Strategy for Implementing Digital Transformation Towards the Potential of Increasing the Economic Performance of Fakfak Regency Communities (Case Study of Teluk Patipi District) - Istiqomah, Titis; Rumagesan, Abdullah; Wihel, Suprijono (ADMAN: Journal of Contemporary Administration and Management, 2024)
The aim of this research is to determine the influence of the extensive development of digitalization facilities being implemented by the Government in the Patipi Bay district to accelerate economic development. This research is descriptive in nature and employs a semi-qualitative analysis approach. Data was obtained through direct observation and interviews with deliberately selected respondents. These interviews, conducted using questionnaires, aimed to explore data related to the research variables. The research variables consist of digitalization techniques and the potential for economic activity. Observation results show that the economic performance of the Patipi Bay district's population remains relatively low. There has been no significant improvement in economic performance over the last few decades, which has impacted local community empowerment and indicators of productive activity. The research concluded that digitalization in the Patipi Bay district must be continually refined. This is a duty and responsibility of the government. The district's abundant natural resources have the potential to become a sustainable economic source for the community. Through digitalization, residents will be able to access numerous sources of information to develop their businesses.